Analysis of the forced response of coupled panels using a hybrid finite element/wave and finite element method. (27th October 2022) - Yang, Yi; Kingan, Michael J.; Mace, Brian R.
Highlights: A method is presented for modelling the forced response of coupled finite panels. The method is straightforward to implement with low computational cost. Complex panels and joints can be modelled straightforwardly. The forced response of connected CLT panels is calculated. The response is analysed in terms of excited and coupled wavemodes in each panel. Abstract: This paper presents a hybrid finite element/wave and finite element method for predicting the forced response of coupled rectangular panels subjected to a time-harmonic point force. The panels are coupled by a joint having an arbitrarily-shaped cross-section. The panels are assumed to be uniform and homogenous in-plane and the through-thickness construction can be arbitrarily complicated. The method represents the response of the panels as a sum of wave modes and determines the characteristics of each wavemode in order to calculate the structural response. Examples of coupled thin plates and cross-laminated timber panels connected by an L joint are presented to illustrate this method. For the coupled thin plates, results calculated using the method are compared with analytical expressions and show excellent agreement. The forced response of the coupled cross-laminated timber panel system is found straightforwardly at low computational cost.